2007
DOI: 10.1111/j.1600-0501.2007.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of panoramic radiographs in the preoperative planning of posterior mandibular implants: a prospective clinical study of 1527 consecutively treated patients

Abstract: Panoramic examination can be considered a safe preoperative evaluation procedure for routine posterior mandibular implant placement. Panoramic radiography is a quick, simple, low-cost and low-dose presurgical diagnostic tool. When a safety margin of at least 2 mm above the mandibular canal is respected, panoramic radiography appears to be sufficient to evaluate available bone height prior to insertion of posterior mandibular implants; cross-sectional imaging techniques may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
1
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 24 publications
(38 reference statements)
6
111
1
12
Order By: Relevance
“…Thus, it can be assumed that the inter-observer agreement using digital panoramas showed good reliability. The prospective clinical study using the panoramic radiographs to evaluate the preoperative planning of posterior mandibular implants showed that panoramic radiographs appeared to be sufficient to evaluate available bone height before insertion of posterior mandibular implants when a safety margin of at least 2 mm above the mandibular canal is respected (15). Taken together, it can be concluded that panoramic radiographs showed sufficient accuracy with good interexaminer agreement.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, it can be assumed that the inter-observer agreement using digital panoramas showed good reliability. The prospective clinical study using the panoramic radiographs to evaluate the preoperative planning of posterior mandibular implants showed that panoramic radiographs appeared to be sufficient to evaluate available bone height before insertion of posterior mandibular implants when a safety margin of at least 2 mm above the mandibular canal is respected (15). Taken together, it can be concluded that panoramic radiographs showed sufficient accuracy with good interexaminer agreement.…”
Section: Discussionmentioning
confidence: 80%
“…however, although panoramic radiography may provide underestimated bone height values, underestimating is safer than overestimating due to the risk of reaching vital structures (7). Vazquez et al (12) suggested the use of a 2 mm safe margin in the mental foramen region after the magnification image compensation when panoramic radiographs are used and Bahlis et al (13) suggested the same safety margin for surgical purposes when using periapical radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Furthermore, panoramic radiographs have been reported to be sufficiently reliable to evaluate the available bone height before inserting posterior mandibular implants. [4][5][6] Image distortion, due to variations in the degree of magnification in the horizontal and vertical planes, is well described for conventional film-based panoramic radiography.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Furthermore, panoramic radiographs have been reported to be sufficiently reliable to evaluate the available bone height before inserting posterior mandibular implants. [4][5][6] Image distortion, due to variations in the degree of magnification in the horizontal and vertical planes, is well described for conventional film-based panoramic radiography. [7][8][9][10][11] As direct digital panoramic machines are not significantly different from conventional panoramic units, the degree of vertical magnification due to projection geometry is similar for digital and conventional rotational panoramic radiographs.…”
Section: Introductionmentioning
confidence: 99%